Collection, Presentation and Analysis of Multimedia Data with Computers - Thomas Irion (Forum: Qualitative Social Research, 2002)
Most computer-aided research tools for qualitative social research focus on the analysis of verbal data. The growing use of digital technology in traditional video- and audio-work has opened up new possibilities for the analysis of multimedia data in qualitative research. This development presents new challenges for researchers and the research tools they use. This article examines the possibilities and limitations associated with the use of multimedia data in qualitative research and the new opportunities in data collection and analysis are discussed. The second section deals with the collection of multimedia data. The third section examines the computer aided data analysis of multimedia data. It is argued that the use of special methods of transcription is more relevant to deductively oriented research projects. There are few software applications for data analysis of multimedia data. A possible way to create more applications is the modular use of software tools. This proposal is illustrated with an example. URN: urn:nbn:de:0114-fqs0202165